Produktivitas Mosher II Penambangan Silika Tambang Kuari PT Semen Padang - Chita Annisa Putri; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2023)
In the Industrial Field Practices that have been carried out at PT Semen Padang, the author has an interest in the disturbances that occur in the Mobile crusher. The Mobile Crusher (Mosher II) is a silica processing tool which has the function of separating silica material from other materials such as tuff and basalt to further refine the silica material so that it meets the requirements for distribution to factories. During its implementation in the field, problems were encountered related to the crushing of silica materials, including damage to the chain feeder and a clogged chute, so that the operation of Mosher II had to be temporarily stopped. The obstacles encountered will affect the productivity of Mosher II and the amount of efficient working time. From Industrial Field Practice Activities in January 2018 the productivity target of Mosher II for silica mining is 900 tons/hour. The actual data obtained in the field for the productivity of Mosher II as a silica processing tool did not reach the desired target of 837.82 tons/hour. For the Mosher II operating time obtained 89.167 hours. And the efficiency of Mosher II is 43.96%